IMPACT OF THE COVID-19 PANDEMIC ON FOOD SECURITY AND LIVELIHOODS IN NIGERIA'S FORMAL AND INFORMAL SECTORS - Belewu, Kafayat Y; Adewale, Caleb I; Akosile, Nusirat O (Agricultural Socio-Economics Journal, 2026)
The COVID-19 pandemic had significant impacts on food security and livelihoods globally, with profound consequences in developing economies like Nigeria. This study investigates the effects of the pandemic on food security, household nutrition, and livelihood status, particularly focusing on both the formal and informal sectors in Lagos State, Nigeria. The disruption of food systems, restrictions on movement, and economic instability exacerbated food insecurity, particularly among low-income households. The research identifies key factors such as the increase in food prices, scarcity of food items, and malnutrition, which severely affected the socio-economic conditions of the respondents. Findings indicate that households were forced to adapt by reducing food consumption, shifting towards cheaper and less nutritious food options, and facing increased poverty levels. The pandemic's impact on livelihood strategies, including job losses and migration towards farming, further aggravated the situation. The study highlights the need for effective policies to support vulnerable households, enhance food production resilience, and strengthen local food systems to mitigate future crises. Recommendations include expanding social protection programs, supporting smallholder farmers, and promoting nutritional education to ensure food security and sustainable livelihoods in the post-pandemic economy.